2017
DOI: 10.1177/0022034517725692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Eda Pathway on Tooth Root Development

Abstract: The Eda pathway ( Eda, Edar, Edaradd) plays an important role in tooth development, determining tooth number, crown shape, and enamel formation. Here we show that the Eda pathway also plays a key role in root development. Edar (the receptor) is expressed in Hertwig's epithelial root sheath (HERS) during root development, with mutant mice showing a high incidence of taurodontism: large pulp chambers lacking or showing delayed bifurcation or trifurcation of the roots. The mouse upper second molars in the Eda pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…For instance, the Eda pathway is specifically active in HERS in mouse molars. Cell proliferation activity is altered in the dental mesenchyme in Eda mutant molars with delayed furcation formation, suggesting that epithelial-derived signals may regulate furcation development through epithelial-mesenchymal interaction (Fons Romero et al, 2017). Recent studies have begun to explore the role of the dental mesenchyme in regulating root patterning and furcation development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Eda pathway is specifically active in HERS in mouse molars. Cell proliferation activity is altered in the dental mesenchyme in Eda mutant molars with delayed furcation formation, suggesting that epithelial-derived signals may regulate furcation development through epithelial-mesenchymal interaction (Fons Romero et al, 2017). Recent studies have begun to explore the role of the dental mesenchyme in regulating root patterning and furcation development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms involved in HERS regulation of furcation development remain unknown. Although previous studies have shown that changes in cell proliferation activity in the dental mesenchyme can lead to furcation defects (Fons Romero et al, 2017; Sohn et al, 2014), it is not clear whether the instructions that ultimately determine root furcation development and number reside in the dental mesenchyme or epithelium.…”
Section: Introductionmentioning
confidence: 97%
“…Late timing or failure of Hertwig’s epithelial root sheath (HERS) invagination may be responsible for the apical shift of the root furcation in taurodontism (Yang et al, 2015). Pathogenic variants in genes in the Eda receptor ligand pair, particularly Eda and Edar, may result in taurodontism of some molar teeth as a result of changes in the proliferation and angle of HERS (Fons Romero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For BrdU, 2M HCl at 37 o C was used before addition of the primary antibody. In situ hybridization was performed as previously described ( Fons Romero et al, 2017 ). Immunolabelings and in situ hybridization reactions were repeated at least 3 times to confirm the expression patterns.…”
Section: Methodsmentioning
confidence: 99%